Konsumsi Fast-Food, Aktivitas Fisik, dan Prevalensi Overweight saat Pandemi Covid-19 - Lina Agestika; Nyuli Maulani (Sarana Ilmu Indonesia (salnesia), 2022)
During the Covid-19 pandemic, the community's physical activity decreased while fast food is preferable. The imbalance in energy intake could lead to triggering an excess nutritional status. The purpose of the study was to analyze the association between fast-food consumption and physical activity on the nutritional status of students during the Covid-19 pandemic. A cross-sectional study with accidental sampling among 84 students at one of the private Universities located in East Jakarta was conducted. The data were nutritional status, fast-food consumption, and physical activity. Statistical analysis was a chi-square test. Almost one-third of students were overweight (29,8%), more than half of them had low physical activity levels (51,2%) and frequently consumed fast-food (57,2%). Both fast food consumption and physical activity were not different between students with a normal nutritional status and overweight during the Pandemic (p-value>0,05). This concluded that the trend of consuming fast food while performing low physical activity occurred not only for those with overweight but those who have normal nutritional status.